2004
DOI: 10.1093/humrep/deh292
|View full text |Cite
|
Sign up to set email alerts
|

In utero exposure to organochlorines and age at menarche

Abstract: The DDE effect on age at menarche encourages further research about in utero exposures. Prospective studies including the offspring's DDE level before menarche are of particular interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
115
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(123 citation statements)
references
References 61 publications
4
115
0
4
Order By: Relevance
“…Delayed initiation of breast development was found in girls with higher prenatal dioxin exposure . In several other studies, no significant association was found between exposure to persistent chlorinated compounds and timing of puberty, in girls (Blanck et al, 2000;Gladen et al, 2000;Vasiliu et al, 2004) or in boys (Gladen et al, 2000;Mol et al, 2002).…”
Section: Discussionmentioning
confidence: 71%
“…Delayed initiation of breast development was found in girls with higher prenatal dioxin exposure . In several other studies, no significant association was found between exposure to persistent chlorinated compounds and timing of puberty, in girls (Blanck et al, 2000;Gladen et al, 2000;Vasiliu et al, 2004) or in boys (Gladen et al, 2000;Mol et al, 2002).…”
Section: Discussionmentioning
confidence: 71%
“…[99][100][101] Early environmental exposures that mimic estrogens, such as bisphenol A, 102 atrazine, 103 and polyaromatic hydrocarbons, 104 may be related to earlier breast development, thereby putting the rapidly proliferating mammary tissue at risk. Chemicals that are associated with early menarche, such as polybrominated biphenyls 105 and dichlorodiphenyldichloroethylene, 106 are also of interest.…”
Section: Breast Cancermentioning
confidence: 99%
“…that highly exposed females tended to be younger at menarche (Denham et al 2005). Contradictory to this study, Vasiliu et al (Vasiliu et al 2004) found that in utero exposure to DDE, but not PCB, resulted in reduced age at menopause. However, this effect was no longer statistically significant when adjusted for BMI.…”
Section: Discussionmentioning
confidence: 57%